Asymmetric modelling and control of an electronic throttle. (20th April 2015) - Pujol, Gisela; Vidal, Yolanda; Acho, Leonardo; Vargas, Alessandro N.
Summary: This paper presents an improved model for an automotive electronic throttle inspired on the behaviour observed in real‐time experiments. Due to a number of issues, particularly the return‐spring, the performance of the throttle valve depends on whether it is opening or closing. This asymmetric behaviour was taken into account to design a mathematical model of the throttle body and to derive a nonlinear asymmetric Proportional Integral controller. The experimental demonstration suggests that considering an asymmetric term dramatically improves the performance of the controller. Copyright © 2015 John Wiley & Sons, Ltd.